Applied novel functionality in separation procedure from leaching solution of zinc plant residue by using non-aqueous solvent extraction - Fatemeh Badihi; Ali Haghighi Asl; Mehdi Asadollahzadeh; Rezvan Torkaman (Scientific Reports, 2023)
Abstract Traditional solvent extraction (SX) procedures limit metal separation and purification, which consist of the organic and aqueous phases. Because differences in metal ion solvation lead to distinct distribution properties, non-aqueous solvent extraction (NASX) considerably expands the scope of solvent extraction by replacing the aqueous phase with alternate polar solvents. In this study, an experimental design approach used non-aqueous solvent extraction to extract cobalt from zinc plant residue. The aqueous phase comprises ethylene glycol (EG), LiCl and metal ions. In kerosene, D2EHPA, Cyanex272, Cyanex301, and Cyanex302 extractants were used as a less polar organic phase. Various factors were investigated to see how they affected extraction, including solvent type, extractant type and phase ratio, pH, Co(II) concentration, and temperature. The results revealed that at a concentration of 0.05 M, the Cyanex301 extractant could achieve the requisite extraction efficiency in kerosene. The optimal conditions were chosen as the concentration of Cyanex 301 (0.05 M), the concentration of cobalt (833 ppm), the pH (3.5), and the percent of EG (80%). As a result, during the leaching process, these systems are advised for extracting and separating a combination of various metal ions.